Recycling prestressed concrete pile waste to produce green self-compacting concrete - Gritsada Sua-iam; Natt Makul (Journal of Materials Research and Technology, 2023)
Construction and demolition waste is produced in large quantities and constitutes an overlooked resource with significant potential for recycling and reuse. In fact, recycled concrete aggregate (RCA) has a high resource value, although it is also the case that RCA has characteristics that complicate its reuse. This research study looks at the efficacy of producing green self-compacting concrete (SCC) using uniform in-situ prestressed concrete pile waste (RCA) as a replacement for natural aggregate and fly ash (FA) as a replacement for Type 1 Portland cement (OPC). In accordance with the European standard, the workability characteristics of the SCC mixtures were assessed using slump flow, T500 time, J-ring flow, L-box, and V-funnel tests. The hardened properties of compressive strength at 7, 28, and 91 days as well as pulse velocity, Young's modulus, and surface resistivity were also tested. Based on this study, it is possible to produce SCC with both RCA and FA that has better workability and hardened properties than does RCA and also to reduce the negative effects of the latter. SCC produced without coarse natural aggregates showed compressive strength above 50 MPa and maximum compressive strength above 74 MPa at 91 days. SCC produced in this way is, therefore, viable for industrial use.